2021
DOI: 10.1097/ccm.0000000000004950
|View full text |Cite|
|
Sign up to set email alerts
|

A Systematic Review of the Incidence and Outcomes of In-Hospital Cardiac Arrests in Patients With Coronavirus Disease 2019*

Abstract: OBJECTIVES: To investigate the incidence, characteristics, and outcomes of in-hospital cardiac arrest in patients with coronavirus disease 2019 and to describe the characteristics and outcomes for patients with in-hospital cardiac arrest within the ICU, compared with non-ICU patients with in-hospital cardiac arrest. Finally, we evaluated outcomes stratified by age. DATA SOURCES: A systematic review of PubMed, EMBASE, and preprint websites was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 45 publications
1
16
2
Order By: Relevance
“…This differs from data from a US registry which indicate an increase in non-shockable rhythms during the pandemic period 5 . Other studies of IHCA during the COVID-19 pandemic have documented an increase in the proportion of non-shockable rhythms but are studies of patients with confirmed COVID-19 infection unlike our study which involved all patients with an IHCA 1 .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This differs from data from a US registry which indicate an increase in non-shockable rhythms during the pandemic period 5 . Other studies of IHCA during the COVID-19 pandemic have documented an increase in the proportion of non-shockable rhythms but are studies of patients with confirmed COVID-19 infection unlike our study which involved all patients with an IHCA 1 .…”
Section: Discussionmentioning
confidence: 77%
“…Evidence suggests an impact of SARS-COV-2 infection on the risk of in-hospital cardiac arrest (IHCA) and the processes of care and patient outcomes following IHCA. [1] , [2] In the United Kingdom (UK), measures to help hospitals cope with the pandemic included cancelling elective surgery, discharging many hospital patients, and preparing for an increase in patients requiring respiratory support, all of which may have altered the case mix of the inpatient population. Additionally, hospital staff were deployed to more acute, and often less familiar, clinical areas.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the incidence of overall in-ICU CA and those with CPR attempt was 14, and 8%, respectively, in the only other published multicenter in-ICU CA cohort of patients admitted for COVID-19 in USA [ 16 ]. Moreover, a recent review of the incidence of IHCA in patient with COVID-19 reported between 8 and 11% among ICU patients [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, this difference in outcome could mainly be explained by our inclusion criteria and selection of patients: only in-ICU CA patients with CPR attempt have been included here in our study. By contrast, most of previous studies have included a limited number of in-ICU CA (with or without CPR attempt) or only IHCA in unmonitored wards which are known to be associated with poorer outcome [ 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…A few publications have started emerging regarding outcomes of in-hospital cardiac arrest during the COVID-19 pandemic yielding information regarding gender, age, common initial rhythm, survival to discharge, or achievement of ROSC. 3,[10][11][12][13][14] To the best of our knowledge, this is the first study reporting the epidemiology and outcomes of IHCA pre-and during pandemic in Pakistan.…”
Section: Discussionmentioning
confidence: 99%